Design framework for ablution spaces in mosques in Malaysia - Haraty, Hayder Jawad Shakir (2019)
Mosques are places for Muslim prayers and other social activities to be performed. They are built to worship the Almighty Allah at all times, as well as for providing an environment that responds to the needs of devotees and educating the future generation by the Quranic verses and the Prophet’s teachings. Deriving from the Holy Quran and the Prophet, purity is compulsory at all times for Muslims, and it has many denotations that are applicable during prayers and the day. The ablution room is integrated into all mosque designs because it is an unseparated element. Malaysian mosques have been questioned in their application of some of the Islamic regulations to uniform a space that is hygienically clean, and that can respond to the needs of Muslims. The design of the ablution room in Malaysian mosques is encountering a serious issue related to the spaces’ hygiene. Although the ablution room has been designed to respond to a Muslim’s need to conduct the ablution practice and to clean a person spiritually and physically, several problems related to its design aspects were revealed. This research investigates the cleanliness of the Malaysian ablution space. It examines how the design aspects of the ablution rooms of the Iconic Malaysian Mosques impacts the cleanliness of the area and its users. Five case studies were selected for this study. Three methods of study were utilised: physical observation, architectural drawing analysis, and interviews. Aspects of design form, ventilation, cleaning status and user’s experience were discussed. The findings of this research suggested that the larger mosques in Malaysia were suffering from serious hygiene issues that resulted from many aspects including poor design, ventilation systems and users’ abuse. The research suggested some design guidelines for future and existing ablution areas that would significantly improve the condition hygienically.